The Relationship of Protein Diet with Uric Acid Levels in the Elderly in Outpatient Polyclinics : A Cross-sectional Study - Pratiwi, Meydiana Putri; Saputra, Andre Utama; Safitri, Serli Wulan; Parmin, Selamat (Lentera Perawat, 2025)
Uric acid is a common metabolic disorder among the elderly, often associated with dietary patterns, especially high-purine protein intake. Improper dietary management can worsen uric acid levels and increase the risk of chronic complications. This study aimed to determine the relationship between protein diet and uric acid levels in the elderly at the Outpatient Polyclinic of Mapolda South Sumatra. This research used a quantitative cross-sectional design with purposive sampling involving 54 elderly participants aged ≥60 years diagnosed with uric acid levels. The independent variable was protein diet measured by a questionnaire, and the dependent variable was uric acid level measured using the Glucose Uri Acid (GCU) Easy Touch device. Data were analyzed using the Chi-Square test. Most respondents with poor protein diets (95.7%) had high uric acid levels. Statistical analysis showed a significant relationship between protein diet and uric acid levels (p = 0.001). There is a significant relationship between protein diet and uric acid levels. Elderly individuals with good protein diets tend to have normal uric acid levels. Community-based purine-restricted dietary education and intervention should be strengthened to prevent hyperuricemia among the elderly.